2016
DOI: 10.15408/etk.v15i1.3115
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Literacy to Shariah Financial Service Preferences

Abstract: The purpose of this study was to determine whether the Islamic financial literacy and the indicator as the knowledge, ability or skills and the confidence have a significant effect together and partially to the preferences of using the Islamic financial services. This type of research is descriptive research, while the method of analysis used in this study is the method of binary logistic regression analysis. The data used is primary data by the method of distributing questionnaires to users and non-users of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 5 publications
0
20
1
2
Order By: Relevance
“…They found that the financial literacy was affected by age, education level, and the annual income. Sardiana (2016) stated that the financial literacy could affect the preference and usage of the services. Knowledge is one of the factors that had an impact on the preferences.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the financial literacy was affected by age, education level, and the annual income. Sardiana (2016) stated that the financial literacy could affect the preference and usage of the services. Knowledge is one of the factors that had an impact on the preferences.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was observed that third grade students were at a higher financial literacy level than first and second grade students and male students were higher than female students. Sardiana (2016) argued that Islamic financial literacy consists of three dimensions, including the ability to understand the characteristics of financial products, self-confidence and the level of knowledge about Islamic financial products. It was concluded that self-confidence and ability to understand Islamic financial products had no effect on the choice of Islamic financial products, but knowledge of Islamic financial products was highly effective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finansal ürün ve hizmetlerin bireylerin ihtiyaçlarını karşılamak için geliştirildiğini ve bu ihtiyaçların karşılanmasında kişinin ürün ve hizmetler hakkında bilgi sahibi olma ve özelliklerini anlama yeteneğinin, becerisinin ve özgüveninin olması finansal okuryazarlık olarak tanımlanmaktadır. Đslami finansal ürün ve hizmetler hakkında bilgi sahibi olma ve anlama özelliği ise Đslami finansal okuryazarlık olarak ifade edilmektedir (Sardiana, 2016).…”
Section: đSlami Finansal Okuryazarlıkunclassified